(x-y)(x+y) (x^2+y^2) (x^4+y^4)

### 1 Answer | Add Yours

The trick to this problem is to know what to multiply first.

Difference if square rule states: `(x-y)(x+y)=(x^2-y^2)`

Keeping that in mind, we will work from left to right in order to apply this rule few times without having to do a lot of work.

`(x-y)(x+y)(x^2+y^2)(x^4+y^4)=`

`(x^2-y^2)(x^2+y^2)(x^4+y^4)=`

`(x^4-y^4)(x^4+y^4)=`

`(x^8-y^8)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes